INOVASI KEUANGAN DIGITAL ISLAMIC NETWORK ( DIN) TERHADAP OPTIMALISASI PELAYANAN JASA PERBANKAN DI ERA DIGITAL (STUDI KASUS BANK MUAMALAT ) - Ahmad Takdir (Islamic Banking and Finance, 2021)
This study discusses the Islamic digital network (DIN) innovation for banking service products in the digitalization era at Bank Muamalat KCP Kab.Bone. The objectives of this research are (1). To find out the muamalat digital Islamic network (DIN) innovation for banking services. (2). To find out the impact of the muamalat digital Islamic network (DIN) innovation on the optimization of banking services in the digitalization era. The type of this research is the type of field research (field research) with the research approach used is a qualitative approach. This technique is used to describe the data that researchers collect, both data from interviews, observations and documentation during research at Bank Muamalat KCP Kab. Bones. The results of this study indicate that (1).Muamalat digital Islamic network (DIN) is a mobile banking muamalat which is then transformed into a digital Islamic network muamalat. In the application of the muamalat digital Islamic network (DIN) which was introduced and implemented throughout Indonesia on November 14, 2019, Bank Muamalat targets to provide convenient and uncomplicated services so that it has positive implications for customers. This product is upgraded so that it is not inferior to other products and so that it can compete in the digital 4.0 era (2). The impact of the implementation of the Islamic digital Islamic network (DIN) on the optimization of banking services in the digitalization era are: the use of the digital Islamic network (DIN) muamalat provides easy service to customers, saves time, provide security to customers and provide satisfaction to customers. Thus the creation of effectiveness and efficiency in the application of digital Islamic network (DIN) muamalat, there will be optimization of banking services in the digital era.